Which foreigners are worth wooing? A meta-analysis of vertical spillovers from FDI - Tomáš Havránek; Zuzana Iršová (Charles University in Prague, Institute of Economic Studies (IES), 2010)
The principal argument for subsidizing foreign investment is the assumed spillover of technology to local firms. Yet researchers report mixed results on spillovers. To examine the phenomenon in a systematic way, we collected 3,626 estimates from 57 empirical studies on between-sector spillovers and reviewed the literature quantitatively. Our results indicate that model misspecifications reduce the reported estimates, but that journals select relatively large estimates for publication. The underlying spillover to suppliers is positive and economically significant, whereas the spillover to buyers is insignificant. Greater spillovers are generated by investors that come from distant countries and that have only slight technological advantages over local firms. In addition, greater spillovers are received by countries that have underdeveloped financial systems and that are open to international trade.
Keywords: C83; F23; 330; foreign direct investment; productivity; spillovers; meta-analysis; publication selection bias; Direktinvestition; Spillover-Effekt; Technologietransfer; Produktivität; Meta-Analyse; Bibliometrie; Bias